2016
DOI: 10.1186/s13033-016-0071-9
|View full text |Cite
|
Sign up to set email alerts
|

‘Opening up the mind’: problem-solving therapy delivered by female lay health workers to improve access to evidence-based care for depression and other common mental disorders through the Friendship Bench Project in Zimbabwe

Abstract: BackgroundThere are few accounts of evidence-based interventions for depression and other common mental disorders (CMDs) in primary care in low-income countries. The Friendship Bench Project is a collaborative care mental health intervention in primary care in Harare for CMDs which began as a pilot in 2006.Case presentationWe employed a mixture of quantitative and qualitative approaches to investigate the project’s acceptability and implementation, 4–8 years after the initial pilot study. We carried out basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 19 publications
2
80
0
16
Order By: Relevance
“…This nding is consistent with other studies which demonstrated that perceived and internalized stigma was signi cantly related to poor disclosure pattern among HIV infected women (31)(32)(33). A qualitative study on depression suggested the involvement of female lay health workers (34) for depression management to enhance acceptability and minimize fear of stigma (35,36).…”
Section: Discussionsupporting
confidence: 90%
“…This nding is consistent with other studies which demonstrated that perceived and internalized stigma was signi cantly related to poor disclosure pattern among HIV infected women (31)(32)(33). A qualitative study on depression suggested the involvement of female lay health workers (34) for depression management to enhance acceptability and minimize fear of stigma (35,36).…”
Section: Discussionsupporting
confidence: 90%
“…Chatterjee et al (2008) reported penetration as the percentage of patients (53%) who tested positive for a common mental disorderincluding depressionwho received the first session of psycho-education in their project testing the revision of professional roles (task-shifting) for a multicomponent depression intervention in routine primary care in India. Abas et al (2016) reported on the quantitative sustainability of 'Friendship Bench' project activities up to 8 years after the initial pilot project ended and the depression intervention was formally integrated into routine care settings in Zimbabwe.…”
Section: Implementation Outcome Characteristicsmentioning
confidence: 99%
“…10,11 A problem-solving therapy intervention locally termed the Friendship Bench has been shown in piloting to be acceptable for LHWs to deliver in Zimbabwe, with promising results. 7,12,13 In the Friendship Bench model, trained and supervised LHWs provided 6 sessions of individual problemsolving therapy to all patients with common mental disorders and referred those not improving or with suicidal ideation to their immediate supervisors for treatment adjustments. 14 Participants were also invited to an optional 6-session peerled group support program.…”
mentioning
confidence: 99%